2017
DOI: 10.1002/cam4.1154
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of parotid area lymph node metastases after preliminary diagnosis of nasopharyngeal carcinoma: a propensity score matching study

Abstract: Parotid area lymph node (PLN) metastasis in nasopharyngeal carcinoma (NPC) is rare, and its prognosis remains largely unknown. Our study aimed to investigate the prognostic value and staging categories of PLN metastasis in patients with NPC and treated with intensity‐modulated radiation therapy (IMRT), to provide a reference for clinical treatment for NPC with PLN metastasis. Records for 1616 untreated NPC patients without distant metastasis was retrospectively reviewed. All patients underwent magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
(40 reference statements)
1
13
1
Order By: Relevance
“…PSM has been widely used in several areas of medical research including studies to assess factors associated with cancer survival 25, 26, 27, 28, 29. In our study, after 1:1 matching, married patients showed survival advantage over unmarried patients.…”
Section: Discussionmentioning
confidence: 99%
“…PSM has been widely used in several areas of medical research including studies to assess factors associated with cancer survival 25, 26, 27, 28, 29. In our study, after 1:1 matching, married patients showed survival advantage over unmarried patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et et al [15] verified that PLN group had a poorer DMFS than N2 disease but was close to N3 disease. Similarly, Xu et al [16] confirmed that the 5-year DMFS and regional relapse-free survival (RRFS) rates in case with PLN involvement were significantly worse than N2 disease but similar to N3 disease. Meanwhile, the 5-year OS and PFS were consistent with N2 disease.…”
Section: Discussionmentioning
confidence: 80%
“…Initial PLN metastasis is far less common in NPC patients with an incidence rate of 1%-3.4% in previous studies [ 4 - 7 ] and 2.3% in our study. Due to the low incidence of PLN involvement, there was a paucity of data addressing the prognostic significance and appropriate clinical classification methods for PLN metastasis [ 15 , 16 ]. Zhang et et al [ 15 ] verified that PLN group had a poorer DMFS than N2 disease but was close to N3 disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLN metastasis of NPC was recommended to assess as N3 and treat with aggressive concurrent chemoradiotherapy to decrease the possibility of distant metastasis. Parotidectomy is a choice for treatment-resistant (CRT) cases, as the cases with NPC and Rhabdomyosarcoma in the present series [31][32][33].…”
mentioning
confidence: 87%